Primary Coenzyme Q10 Deficiency: An Update - David Mantle; Lauren Millichap; Jesus Castro-Marrero; Iain P. Hargreaves (MDPI AG, 2023)
Coenzyme Q10 (CoQ10) has a number of vital functions in all cells, both mitochondrial and extra-mitochondrial. In addition to its key role in mitochondrial oxidative phosphorylation, CoQ10 serves as a lipid soluble antioxidant and plays an important role in fatty acid beta-oxidation and pyrimidine and lysosomal metabolism, as well as directly mediating the expression of a number of genes, including those involved in inflammation. Due to the multiplicity of roles in cell function, it is not surprising that a deficiency in CoQ10 has been implicated in the pathogenesis of a wide range of disorders. CoQ10 deficiency is broadly divided into primary and secondary types. Primary CoQ10 deficiency results from mutations in genes involved in the CoQ10 biosynthetic pathway. In man, at least 10 genes are required for the biosynthesis of functional CoQ10, a mutation in any one of which can result in a deficit in CoQ10 status. Patients may respond well to oral CoQ10 supplementation, although the condition must be recognised sufficiently early, before irreversible tissue damage has occurred. In this article, we have reviewed clinical studies (up to March 2023) relating to the identification of these deficiencies, and the therapeutic outcomes of CoQ10 supplementation; we have attempted to resolve the disparities between previous review articles regarding the usefulness or otherwise of CoQ10 supplementation in these disorders. In addition, we have highlighted several of the potential problems relating to CoQ10 supplementation in primary CoQ10 deficiency, as well as identifying unresolved issues relating to these disorders that require further research.